1986
DOI: 10.1002/pssb.2221350113
|View full text |Cite
|
Sign up to set email alerts
|

Superionic phase transitions in hydrogen bonded crystals

Abstract: A microscopic theory of phase transition in the protonic superionic conductors is proposed. By taking into account short-range proton correlations on hydrogen bonds a order-disorder Slater-type phase transition of first order is obtained. Due to the linear coupling between the order parameter and lattice deformation the phase transition is ferroelastic with a soft elastic coefficient C,, -C12. IIpeAnomeaa MxKpocKonmecKan Teopvrn Qa30~0r-o nepexoAa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…[2][3][4] The roomtemperature phase ͑so-called phase II͒ is monoclinic 2 The superionic phase I above T c ϭ412 K in CsDSO 4 ͑or T c ϭ417 K in CsHSO 4 ͒ is tetragonal with the space group I4 1 /amd and aϭ5.741 Å and cϭ14.315 Å. The first-order superionic phase transition is triggered by an orientational disordering of the SO 4 tetrahedra and a resulting rearrangement of the hydrogen bond network where unfilled deuteron sites appear.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The roomtemperature phase ͑so-called phase II͒ is monoclinic 2 The superionic phase I above T c ϭ412 K in CsDSO 4 ͑or T c ϭ417 K in CsHSO 4 ͒ is tetragonal with the space group I4 1 /amd and aϭ5.741 Å and cϭ14.315 Å. The first-order superionic phase transition is triggered by an orientational disordering of the SO 4 tetrahedra and a resulting rearrangement of the hydrogen bond network where unfilled deuteron sites appear.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a superprotonic transition in CsH 2 PO 4 demonstrates that solid acids, in which all the oxygen atoms are hydrogen bonded at low temperature, can exhibit such transitions. The order−disorder model that is appropriate for describing the high-temperature phase of CsHSO 4 , and presumably, also of M 3 H(XO 4 ) 2 compounds such as Rb 3 H(SeO 4 ) 2 , and which would have ruled out a transition in CsH 2 PO 4 , accordingly does not apply here. In those other materials, there is a close structural relationship between the superprotonic and ordered phases, whereas no such simple relationship appears to exist in CsH 2 PO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Cesium cations reside at sites between these layers. Plakida 10 has treated the superprotonic phase transition in the related compound, CsHSO 4 , in terms of a microscopic model that assumes an order-disorder relationship between the low-and high-temperature phases. Although not stated explicitly, such a model rules out the possibility of a superprotonic transition in a compound such as CsH 2 PO 4 , in which all oxygen atoms participate in hydrogen bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic theory of phase transition in protonic conductors was described as correlation between short range proton and hydrogen bond [8]. It was observed that KHSO4 crystals showed a structural phase transition at 468 K [9]. It is of interest to elucidate the influence of both deuteration and dopant on the please transition temperature.…”
mentioning
confidence: 99%
“…The unit cell dimensions are a = 8. 9, b = 9.19 and c = 18.93~ Sunandana [7] detected the existence of two types of sulphate ions using electron spin resonance technique. In type I forming HSO4-dimers, which are joined through two hydrogen bonds, type II forming a polymeric chain along the a axis by means…”
mentioning
confidence: 99%